2007
DOI: 10.1021/bm070333p
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Interaction between Dendriplexes and Bovine Serum Albumin

Abstract: Dendrimers are new nanotechnological carriers for gene delivery. Short oligodeoxynucleotides (ODNs) are a new class of antisense therapy drugs for cancer and infectious or metabolic diseases. The interactions between short oligodeoxynucleotides (GEM91, CTCTCGCACCCATCTCTCTCCTTCT; SREV, TCGTCGCTGTCTCCGCTTCTTCCTGCCA; unlabeled or fluorescein-labeled), novel water-soluble carbosilane dendrimers, and bovine serum albumin were studied by fluorescence and gel electrophoresis. The molar ratios of the dendrimer/ODN den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…The rest of the dendriplexes formed by dendrimers 1, 2 and 4 afforded analogous results and a more detailed physicochemical study will be published separately. 18 The increase of the fluorescence polarization of fluorescein in the presence of dendrimers (Fig. 6A) or in the presence of BSA (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…The rest of the dendriplexes formed by dendrimers 1, 2 and 4 afforded analogous results and a more detailed physicochemical study will be published separately. 18 The increase of the fluorescence polarization of fluorescein in the presence of dendrimers (Fig. 6A) or in the presence of BSA (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…This observation can be explained based on the existence of a special process in which the surfactant-cobalt(III) complex quenches BSA/HSA via initiation of a static mechanism rather than the dynamic process. 31,32 Similarly the binding number per albumin molecule (n) is around 1, indicating a strong and independent binding site in BSA/HSA for the surfactant-cobalt(III) complex. It is also observed that the binding (K b ) between the protein and the Table 2 The Stern-Volmer quenching constant (K sv ), quenching rate constant (k q ), binding constant (K b ), binding number (n) and the thermodynamic parameters (ΔH°, ΔG°and ΔS°) for the interaction of surfactant-cobalt(III) complexes with BSA/HAS at different temperatures Thermodynamic parameters and nature of the binding forces…”
Section: Analysis Of Quenching and Binding Parametersmentioning
confidence: 99%
“…10 Even though the interaction of dendrimers with bovine serum albumin (BSA) has been reported, the effect of polymer complexation on protein stability and secondary structure is not yet known. 11,12 Serum albumins are the major soluble protein constituents of the circulatory system and have many physiological functions. 13 The most important property of this group of proteins is that they serve as transporters for a variety of compounds.…”
Section: Introductionmentioning
confidence: 99%